Patients discharged from higher‐quality skilled nursing facilities spend more days at home. (26th August 2020) - Simning, Adam; Orth, Jessica; Temkin‐Greener, Helena; Li, Yue
Abstract: Objective: To evaluate the association of skilled nursing facility (SNF) quality with days spent alive in nonmedical settings ("home time") after SNF discharge to the community. Data Sources: Secondary data are from Medicare claims for New York State (NYS) Medicare beneficiaries, the Area Health Resources File, and Nursing Home Compare. Study Design: We estimate home time in the 30‐ and 90‐day periods following SNF discharge. Two‐part zero‐inflated negative binomial regression models characterize the association of SNF quality with home time. Data Extraction Methods: We use Medicare claims data to identify 25 357 NYS fee‐for‐service Medicare beneficiaries aged 65 years and older with an SNF admission for postacute care who were subsequently discharged to home in 2014. Principal Findings: Following 30 and 90 days after SNF discharge, the average home time is 28.0 (SD = 6.1) and 81.6 (SD = 20.2) days, respectively. A number of patient‐ and SNF‐level factors are associated with home time. In particular, within 30 and 90 days of discharge, respectively, patients discharged from 2‐ to 5‐star SNFs spend 1.2‐1.5 ( P  < .001) and 3.2‐4.3 ( P  < .001) more days at home than those discharged from 1‐star (lowest quality) SNFs. Conclusions: Improved understanding of what is contributing to differences in home time could help guide efforts into optimizing post‐SNF discharge outcomes.